(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with the concepts of upper s-(τ_1,τ_2)-continuous multifunctions and lower s-(τ_1,τ_2)-continuous multifunctions. Moreover, several characterizations and some properties concerning upper s-(τ_1,τ_2)-continuous multifunctions and lower s-(τ_1,τ_2)-continuous multifunctions are investigated.